2023
DOI: 10.1039/d3ra03260d
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biosynthesized bimetallic ZnO@SeO nanoparticles from pomegranate peel extracts: antibacterial, antifungal and anticancer activities

Abstract: Sustainable bimetallic nanoparticles (NPs) have attracted particular attention in the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…Since, the peaks were observed in our study as follows 23.8 o , 29.07 o , 53.3 o and 67.9 o responsible for the planes of (1 0 0), (1 1 1), (3 1 1), and (4 0 0), the same has been compared with the previous studies ( Taha et al, 2019 ; Mirzaei et al, 2021 ). In addition, the ZnO nanoparticle peaks were confirmed the presence of bi-metallic patterns at this range 54, 66 and 69 and same have been discussed in the Hashem et al (2023) . The X-ray diffraction (XRD) peaks of the Se-doped nanoparticles (NPs) exhibit widening, and reduced intensity compared to the pristine ZnO NPs ( Taha et al, 2019 ).…”
Section: Resultssupporting
confidence: 79%
“…Since, the peaks were observed in our study as follows 23.8 o , 29.07 o , 53.3 o and 67.9 o responsible for the planes of (1 0 0), (1 1 1), (3 1 1), and (4 0 0), the same has been compared with the previous studies ( Taha et al, 2019 ; Mirzaei et al, 2021 ). In addition, the ZnO nanoparticle peaks were confirmed the presence of bi-metallic patterns at this range 54, 66 and 69 and same have been discussed in the Hashem et al (2023) . The X-ray diffraction (XRD) peaks of the Se-doped nanoparticles (NPs) exhibit widening, and reduced intensity compared to the pristine ZnO NPs ( Taha et al, 2019 ).…”
Section: Resultssupporting
confidence: 79%
“…The use of artificial neural networks and surface response methodology in the prediction and optimization of the biopolymer composite properties also adds value to this study. Overall, this study has the potential to contribute to the development of sustainable 71 and eco-friendly materials with enhanced properties and lower environmental impact.…”
Section: Introductionmentioning
confidence: 96%
“…22 ZnO nanoparticles have taken credit for their antimicrobial and antibacterial characteristics and are widely used for packaging, antifouling, and biomedical purposes. [23][24][25] The effect of ZnO as an antimicrobial agent on the semiconductor material was investigated using a biofilm reactor with and without ZnO coating. 26 It was observed that bacterial biofilm growth was reduced by ZnO coating application.…”
Section: Introductionmentioning
confidence: 99%